Penerapan Metode First In First Out Pada Sistem Manajemen Persediaan Stok Janti Park - Rafinda Shinta; Budi Hartanto; Yustina Retno Wahyu Utami (Redtech Putra Benua, 2024)
In meeting consumer needs, optimal inventory management is needed so that there is no shortage of goods resulting in loss of consumers and profit opportunities. This study aims to apply the stock inventory management method at Janti Park by creating an inventory management application that can be used as a basis for controlling and optimizing stock inventory at Janti Park. The method used to analyze the problem is Fishbone Analysis. Data collection methods through interviews, observations, and literature studies. Then the method used for system development is Waterfall, and uses the First In First Out method in managing inventory data. At the system testing stage, the method used is Black Box Testing to test functionality and a Likert scale questionnaire to test validity. The results obtained from this research are in the form of a website-based inventory management application and produce output in the form of reports on purchasing and issuing goods transactions. Based on the results of the tests that have been carried out, it is proven that the First In First Out method can be applied to the Janti Park inventory management system with a system validity test result of 90.8%, with very agreeing criteria.